2023
DOI: 10.1029/2022jc019618
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Dynamics of the Interannual Eddy Kinetic Energy Variation in the Central Pacific Sector of the Southern Ocean

Guanqi Fu,
Yang Yang,
X. San Liang
et al.

Abstract: Mesoscale eddies play a crucial role in the dynamical balance of the Southern Ocean (SO) circulation. Yet, it remains unclear why the SO transient eddy activity has significant variations on interannual time scales, and to what extent these low‐frequency variations are attributed to wind forcing changes. Here we use a functional analysis tool, namely, the multiscale window transform (MWT), the MWT‐based theory of canonical transfer and a time‐dependent energetics framework to investigate these issues. Our focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…48670/moi-00021) acquired from Copernicus Marine Environment Monitoring Service (CMEMS) is employed to investigate the time-varying energetics, limited by the scarcity of in-situ observation in polar regions. The GLORYS12V1 is a global ocean eddy-resolving reanalysis product with a horizontal resolution of 1/12°× 1/12°a nd 50 vertical levels, spanning the altimetry era from 1993 onward, which has been used to analyze energetics in the Southern Ocean (G. Fu et al, 2023). Utilized three-dimensional monthly and daily variables including sea surface height (SSH), current velocity, potential temperature, and salinity across all vertical levels from 1993 to 2020.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…48670/moi-00021) acquired from Copernicus Marine Environment Monitoring Service (CMEMS) is employed to investigate the time-varying energetics, limited by the scarcity of in-situ observation in polar regions. The GLORYS12V1 is a global ocean eddy-resolving reanalysis product with a horizontal resolution of 1/12°× 1/12°a nd 50 vertical levels, spanning the altimetry era from 1993 onward, which has been used to analyze energetics in the Southern Ocean (G. Fu et al, 2023). Utilized three-dimensional monthly and daily variables including sea surface height (SSH), current velocity, potential temperature, and salinity across all vertical levels from 1993 to 2020.…”
Section: Methodsmentioning
confidence: 99%
“…The Lorenz energy cycle (Lorenz, 1955) is an effective approach to investigating the variability of a current system and quantitatively describing energy transfer among reservoirs, providing insights into the underlying ocean dynamics (e.g., Dong et al, 2022;Ivchenko et al, 1997;Kang & Curchitser, 2015;Rieck et al, 2015;von Storch et al, 2012). It has been extensively employed in analyzing energetics in the Southern Ocean (e.g., Chen et al, 2014Chen et al, , 2016G. Fu et al, 2023;Youngs et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reanalysis data acquired from the Global Ocean Reanalysis and Simulation (GLORYS12V1) product were used to investigate the time-varying energetics in this study, limited by the scarcity of in-situ observation. This product is the Copernicus Marine Environment Monitoring Service (CMEMS) global ocean eddy-resolving (1/12° horizontal resolution, 50 vertical levels) reanalysis covering the altimetry (1993 onward), which has been used to analyze energetics in the Southern Ocean [Fu et al, 2023]. Utilized monthly and daily variables include sea surface height, current velocity, potential temperature, and practical salinity in all vertical levels, from 1993 to 2020.…”
Section: Methodsmentioning
confidence: 99%
“…The results demonstrated that the westerlies can locally supply sufficient energy to initiate baroclinic instability in the Indian and Pacific sectors of the ACC. In the central Pacific sector, the interannual variation of EKE in the upper ocean layer has revealed that wind stress impacts the variation through both baroclinic and barotropic pathways [Fu et al, 2023]. However, the Indian sector remains poorly explored.…”
Section: Introductionmentioning
confidence: 99%